Exploring the theoretical relationship between brand innovation and brand authenticity: a case study of a South African brand, Joe Public United - Mahoney, Wendy (The IIE, 2020)
Rapid changes in the global business landscape over recent years has changed the way business is done and understood, necessitating a new approach to brand innovation. Current theorising on brand innovation and brand authenticity implies that there is a theoretical relationship between brand innovation and brand authenticity although this relationship is, at present, not clearly defined nor discussed. Brand authenticity is embodied through consistent action evidenced in the brand’s communication with its stakeholders. By exploring the relationship between brand innovation and brand authenticity a new and novel approach to innovation is proposed in this study. Against the backdrop of the Fourth Industrial Revolution, innovation has become critical and hence, it is relevant and important to contribute to the understanding of brand innovation at present. For this purpose, a case study was conducted on a known innovative South African brand, Joe Public United (JPU), who won agency of the year for the second year in a row in 2019 at the Loeries. This study critically assesses the brand’s communication of its purpose and values as the vehicle of its authenticity driven by its leadership.The results show a clear alignment amongst the brand’s leadership with respect to its purpose and values, indicating evidence of authentic communication and thus establishing the existence of a relationship between brand innovation and brand authenticity. What was of greater insight though was more The kinds of values emphasised were even more significant as it was found that the brand’s focus was on self-excellence achieved through respect and integrity. The values focused on simultaneously encapsulate authenticity, indicating a clear link between brand innovation and brand authenticity. This link becomes clear in the display of the value of authenticity in service, rather than the communication of the brand’s purpose and values. In the case of JPU the key value in this regard was respect in that is seen to be the fuel that ignites innovation in this case study. Since servant-hood alone is not enough, JPU is committed operate at their best so that their service can be the best. Furthermore, the values of respect and the corresponding focus on excellence is governed by the value of integrity and the upward mobility of all stakeholders in the ecosystem. These insights are of great value to the subject of brand innovation. This study shows that the value set is more significant than individuals’ values. The findings in this study show how a focus on all three values contribute to brand innovation.
Keywords: Brand; Brand authenticity; Brand innovation; Brand purpose; Brand value; Brand communication; Brand leadership